POLYTHERMS OF ANGLES OF WETTING OF POROUS NICKEL BY TIN-BARIUM AND INDIUM-SODIUM MELTS - A.Z. Kashezhev; R.A. Kutuev; A.R. Manukyants; M.Kh.Ponegev; V.A. Sozaev; A.Kh. Shermetov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2014)
The polytherms of angles of wetting of the porous carbonyl nickel (with 30% porosity) by tin-barium and indium-sodium melts have been studied for the first time. The temperature thresholds of the beginning of wetting have been discovered:T>475°C in case of tin-barium melts and T>250°C in case of indium-sodium ones. The bunch-shaped arrangements of intermetallics In8Na5 with sizes 7-9 microns have been revealed on the surface of the porous nickel wetted by the melt In-0,5 wt.% Na using the raster electron microscopy.